If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3(2x + 1) = 2x + 8 Reorder the terms: x + 3(1 + 2x) = 2x + 8 x + (1 * 3 + 2x * 3) = 2x + 8 x + (3 + 6x) = 2x + 8 Reorder the terms: 3 + x + 6x = 2x + 8 Combine like terms: x + 6x = 7x 3 + 7x = 2x + 8 Reorder the terms: 3 + 7x = 8 + 2x Solving 3 + 7x = 8 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 3 + 7x + -2x = 8 + 2x + -2x Combine like terms: 7x + -2x = 5x 3 + 5x = 8 + 2x + -2x Combine like terms: 2x + -2x = 0 3 + 5x = 8 + 0 3 + 5x = 8 Add '-3' to each side of the equation. 3 + -3 + 5x = 8 + -3 Combine like terms: 3 + -3 = 0 0 + 5x = 8 + -3 5x = 8 + -3 Combine like terms: 8 + -3 = 5 5x = 5 Divide each side by '5'. x = 1 Simplifying x = 1
| -3ln(x+1)=2 | | 2b+16=4b | | 9y+53=17 | | 13x^2+22=1234 | | (2b+4)(4b+6)= | | 2y^8-8xy^9=0 | | -27=3+5x | | 5(10x+9m-2m)= | | 3t^2-375=0 | | 5(x+3)-10=35 | | 8a^2-10a= | | 9(5-2m)=-7(m-2) | | S^5=s^3 | | 0=5X^2-22X+8 | | 3x-14+8x=41 | | 0=5X^2-18X-8 | | 24-[1+6y-2(y+2)]=4(3y-6)-[7(y-1)-10y+19] | | X^2-x=2x^2-2 | | 3(c-4)=4(c-7) | | 6y=8-9+6 | | 7(c-4)+8=6+c-26 | | -7z^2-14z-13=0 | | -15+3k=k-3k | | -15+3k=-3k | | 2h+5(1.5)=4h+2(1.50) | | -16=16(h-3) | | 0.333x-3=1.333x | | -16=16h(h-3) | | -32=8(y+4) | | 6x-(4x-5)=23 | | 1x^2+6x-7=0 | | 8(6-x)-5=-21 |